Study on the method of improving the heating effect of Korean Ondol - Myong Ho Ri; Phyong Guk Om (International Journal of Architecture and Urbanism, 2026)
In this paper, we investigated a new style of Ondol (Ondol is the unique Korean heating system that heats the floor surface.) [1] that can increase the temperature of the floor surface and the room by an average of 3-4°C while consuming the same quantity of fuel in the Korean Ondol heating. For this purpose, the Ondol floor is divided into the main zone where people are mainly active and the secondary zone where furniture are located. Then, heating only in the main zone and not in the secondary, the same fuel is consumed and a better thermal comfort is provided for human activity. And the bottom of the Ondol is bordered by the ground, and the division of the Ondol into the main and secondary zones reduces unnecessary heat losses to the ground floor, thus effectively providing heating with the same fuel.